Active disturbance rejection generalized predictive control for a high purity distillation column process with time delay. (21st August 2019) - Cheng, Yun; Chen, Zengqiang; Sun, Mingwei; Sun, Qinglin
Abstract : High purity distillation processes have been widely used in the chemical industry. These processes have unique characteristics including higher order, nonlinearity, strong coupling, and time delay. In order to overcome these control issues, an active disturbance rejection generalized predictive control strategy is designed for the distillation column with time delay. The strategy combines the structures of both active disturbance rejection control and generalized predictive control. A delayed designed extended state observer can estimate the model uncertainty and external disturbance, and a non‐incremental generalized predictive control is proposed to deal with the integrators with time delay. Therefore, it rejects disturbances well and has the capability of overcoming time delay. The computation load is also less than the generalized predictive control. In the simulation experiments, the proposed strategy is compared with robust control and model predictive control. The results illustrate that the proposed control strategy has improved robustness performance in dealing with model uncertainties, various disturbances, and time delay.